Information Needs and Contextualization in the Consultation Process of Dictionaries that are Linked to e-Texts - Bothma, Theo J.D.; Gouws, Rufus H. (Lexikos, 2022)
This article focuses on various aspects regarding contextualization when e-texts are linked to integrated dictionaries. The article responds to a twofold problem statement: (1) Dictionaries linked to e-texts do not sufficiently take into account the contextualization and cotextualization of words when providing information to users. (2) The integrated dictionary may contain the items needed for contextualization and cotextualization, but the e-device cannot interpret the context of a word and link the word to the relevant item in the dictionary article. The aim of the article is to show the need of linking a word from a text on an e-device to the correct sense in the integrated dictionary. This presupposes dynamic dictionary articles and lexicographic structures in which a relation between words in an e-text and user-specified lexicographic sources is established. Some existing projects that perform such linking are discussed and evaluated. Based on these results this article makes some suggestions. It is foreseen that there will be a "black box" of software between the selected word and the dictionary that will determine the correct lemma and sense to be selected from the e-dictionary. Having discussed various alternatives, the article suggests parallel contextualization between the dictionary and the software of the e‑device. Many aspects discussed in this article require further research. Relevant proposals are made with regard to this research. Keywords: context, contextualization, cotext, dictionary consultation, e-device, e-reader, e-text, integrated dictionary, lexicographic needs, linking, parallel contextualization, text reception